2005
DOI: 10.1002/gps.1401
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial aldehyde dehydrogenase polymorphism is not associated with incidence of Alzheimer's disease

Abstract: ALDH2*2 does not seem to be important in the etiology of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…But the subsequent studies in Koreans didn't get the similar results [13,14]. To our knowledge, there has not been any association analysis of ALDH2 1/2 polymorphism with LOAD reported in Chinese.…”
Section: Introductioncontrasting
confidence: 62%
See 1 more Smart Citation
“…But the subsequent studies in Koreans didn't get the similar results [13,14]. To our knowledge, there has not been any association analysis of ALDH2 1/2 polymorphism with LOAD reported in Chinese.…”
Section: Introductioncontrasting
confidence: 62%
“…But the association studies from Korea failed to establish the statistically significant association between the ALDH2 1/ 2 polymorphism and AD progression [13,14]. These paradox findings may be due to ethnic differences of samples studied.…”
Section: Discussionmentioning
confidence: 89%
“…An association with late-onset AD (LOAD), interacting synergistically with the presence of the apolipoprotein E allele 4 (APOE ε4) has been detected in Japanese and Chinese subjects, whilst it was not reported in a population of Koreans [20][21][22][23][24]. A longitudinal study found that the incidence of AD in healthy participants was not correlated with ALDH polymorphism within 2.4 years [24]. In the mouse model, it has been shown that a deficiency in mitochondrial ALDH2 leads to age dependent memory impairment and increased lipid peroxidation [25].…”
mentioning
confidence: 99%
“…Past studies on ALDH2 have focused on its relation to general cognitive function in patients with Alzheimer's disease (AD), Parkinson's disease (PD), and substance use disorders. Some studies proposed that ALDH2 A allele may be a risk factor of AD [22][23][24], but others disagreed [25][26][27][28]. Of the studies listed above, only Kim et al and Shin et al evaluated the general cognitive function of AD patients, but both of them failed to find a relation between general cognitive function and ALDH2 [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies proposed that ALDH2 A allele may be a risk factor of AD [22][23][24], but others disagreed [25][26][27][28]. Of the studies listed above, only Kim et al and Shin et al evaluated the general cognitive function of AD patients, but both of them failed to find a relation between general cognitive function and ALDH2 [25,26]. Previous studies on ALDH2 and PD have focused on catecholaldehyde hypothesis, which suggested that ALDH2 inactivity may mediate the extent of damage to the dopamine system due to increased levels of toxic aldehydes [13].…”
Section: Introductionmentioning
confidence: 99%